2019
DOI: 10.1108/ijcma-01-2019-0010
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between conflicts and employee perceived job performance

Abstract: Purpose Over 83.72 million Chinese firms employing more than 775 million employees. It is essential to explore employee relationships and conflict management practices in China. Although collectivism can influence employee cognition and emotions, the psychological mechanism that links collectivism and job satisfaction is still unclear. Researchers have found existing empirical findings on conflict–performance relationships to be mixed and inconsistent, and have identified the need to pinpoint the explanatory m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 87 publications
(152 reference statements)
0
25
1
2
Order By: Relevance
“…For example, Danielsson et al (2015) reported that among thousands of participants in their studies over the past two years, 84% had reported being in some type of conflict situation with their coworkers, and about 50% had experienced it on a weekly basis. In addition to its high prevalence, interpersonal conflict has been found to have detrimental effects on employee job attitudes, health and well‐being, nonwork life and performance (for reviews, see Bonaccio et al , 2019; Kuriakose et al , 2019; Notelaers et al , 2018; Ye et al , 2019). In addition to the negative effects of interpersonal conflict on individuals’ work and health‐related outcomes, Zhou et al (2019) suggest that effects of interpersonal conflict at work can spill over to employees’ negative work behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Danielsson et al (2015) reported that among thousands of participants in their studies over the past two years, 84% had reported being in some type of conflict situation with their coworkers, and about 50% had experienced it on a weekly basis. In addition to its high prevalence, interpersonal conflict has been found to have detrimental effects on employee job attitudes, health and well‐being, nonwork life and performance (for reviews, see Bonaccio et al , 2019; Kuriakose et al , 2019; Notelaers et al , 2018; Ye et al , 2019). In addition to the negative effects of interpersonal conflict on individuals’ work and health‐related outcomes, Zhou et al (2019) suggest that effects of interpersonal conflict at work can spill over to employees’ negative work behaviors.…”
Section: Introductionmentioning
confidence: 99%
“…innovative work behavior). Third, scholars have focused on the underlying mechanisms (mediators and moderators) to understand the effect of task conflict on employee attitudes and behaviors (Posthuma et al , 2011; Sonnentag et al , 2013; Lee et al , 2019; Ye et al , 2019). These studies suggest that future researchers should look into developing comprehensive underlying mechanism that could explain the relationship between task conflict and employee positive behaviors.…”
Section: Discussionmentioning
confidence: 99%
“…As conflict is defined as "the process that begins when one party perceives that the other has negatively affected, or is about to negatively affect, something that he or she cares about" (Thomas, 1992, p. 653), we argue that destructive leader behaviour results in various forms of conflict between leader and subordinate, resulting in dissatisfaction with the leader. More specifically, it may lead to relationship conflict, which impacts the satisfaction levels of the subordinate (Ye et al, 2019). On this basis, we propose the first hypothesis: H1.…”
Section: Conceptual Framework and Hypothesis Developmentmentioning
confidence: 94%
“…Destructive leader behaviour and subordinate dissatisfaction Leader behaviour has a huge influence on employee satisfaction (Ye et al, 2019). Schilling (2009) argued that destructive leaders do not facilitate working; rather, they make work more complex and demanding for their subordinates.…”
Section: Conceptual Framework and Hypothesis Developmentmentioning
confidence: 99%